Biomechanical analysis of different badminton forehand overhead strokes of Taiwan elite female players - Tsai, C.-L.; Hsueh, Y.-C.; Pan, K.-M.; Chang, S. S. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The results showed that there were significant differences among the three forehand strokes in the initial shuttle velocity, the initial shuttle angle and the vertical COM velocity at the contact. The subjects manipulate the upper arm flexion angular velocities of the clear and the smash as in the sequence as followed, wrist > elbow > shoulder, it obeyed the rule of kinetic chain. We found that the greatest angular velocity of upper arm movement was happened in the shoulder internal rotation. The strength training on the shoulder would be very important for the badminton players. There were some differences in the kinematics variables between female and male badminton players. For instance as in the initial velocity of the smash, the initial shuttle flight angle between the male and the female. The reasons of the differences between the male and the female players should be investigated in the further studies.